2018
DOI: 10.15345/iojes.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Smartphone Addiction and Perceived Social Support of University Students’

Abstract: The main purpose of this research is to determine the relationship between university students' social support perceptions and smartphone addiction. For this purpose, a quantitative research was carried out. İnönü University students in Turkey are the population of the research and 496 senior students from these students constitute the sample. The data for the study were obtained through the Multidimensional Scale of Perceived Social Support (MSPSS) and The Smartphone Addiction Scale-Short Version (SAS-SV). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 12 Research on smartphone addiction and students’ perception of the support they receive from social relationships indicates that the level of perceived social support of females was statistically higher compared to males, but smartphone addiction levels do not significantly differ based on gender. 32 …”
Section: Gender and Smartphone Addictionmentioning
confidence: 99%
“… 12 Research on smartphone addiction and students’ perception of the support they receive from social relationships indicates that the level of perceived social support of females was statistically higher compared to males, but smartphone addiction levels do not significantly differ based on gender. 32 …”
Section: Gender and Smartphone Addictionmentioning
confidence: 99%
“…Social support could be considered a significant resource to alleviate the negative effects of stressors (Delaney, 2017) it can enhance psychological resilience, hopeful thinking, academic performance, and life satisfaction (Satı & Girgin, 2016;Xiang, Teng, Li, Chen, & Guo, 2020). Numerous past studies have shown that university students with low perceived social support demonstrated high smartphone usage (Celik & Konan, 2019;Konan, Durmuş, Bakır, & Türkoğlu, 2018). In terms of the association between psychological distress and perceived social support, the vulnerability of undergraduates to depressive and anxiety symptoms is closely related to perceived social support (Zhang, Zhang, Zhang, Zhang, & Feng, 2018).…”
Section: Perceived Social Support As a Mediator In The Relationship B...mentioning
confidence: 99%
“…The clinical undergraduates who received high social support demonstrated reduced depression and stress (Kalok et al, 2020). Perceived social support was found to be significantly and negatively correlated with smartphone addiction among university students (Akturk & Budak, 2019;Konan et al, 2018). The relationship between social support and smartphone addiction is cyclical and complex as not only that social support predicted later smartphone addiction; but smartphone addiction also reduced social support over time (Herrero, Urueña, Torres, & Hidalgo, 2019).…”
Section: Perceived Social Support As a Mediator In The Relationship B...mentioning
confidence: 99%
“…Researchers found that perceived social support was a good predictor of problematic internet behavior. Perceived social support can effectively slow down teenagers' deviant behavior on the Internet [9] .…”
Section: Introductionmentioning
confidence: 99%